ASPEK FARMAKOLOGI TETRAHIDROKURKUMIN: METABOLIT UTAMA KURKUMIN - Agung Endro Nugroho (Universitas Islam Indonesia, 2006)
ABSTRACTTetrahydrocurcumin is a main metabolite product from biotransformation process of curcuminin the body. Biotransformation of curcumin is fast and occurred during absorption process ingastrointestinal tract. The biotransformation of curcumin to tetrahydrocurcumin and the stability oftetrahydrocurcumin play important roles in the biological effects of curcumin in the body. Thepresent article discussed about the pharmacological aspects of tetrahydrocurcumin.Tetrahydrocurcumin was reported possessing several pharmacological activities such as:antioxidant, anti-inflammatory, hepatoprotector, anti-allergy, protective for atherosclerosis and renaldamage, and also anticarcinogenesis. It’s main pharmacological activity is antioxidant, which isunderlying and responsible for the other activities. The antioxidant activity of tetrahydrocurcuminwas reported better than this of curcumin. The main factors for the antioxidant or free radicalscavenger effects of tetrahydrocurcumin are it’s aromatic/phenolic hydroxy and -diketon moieties.Key words : tetrahydrokurcumin, curcumin, pharmacology, antioxidant